(untitled) (Bulletin of the International Association for Paleodontology, 2025)
Dental professionals need comprehensive knowledge of both clinical and medicolegal aspects to manage patient care effectively. In Indonesia, diverse geographic and socio-economic conditions in rural, urban, and suburban areas present unique challenges. This study evaluates the medicolegal knowledge and awareness among dental practitioners in these varied practice settings. An observational analytic cross-sectional study was conducted with 274 dental practitioners from Indonesia’s rural, urban, and suburban areas. Data were collected through an online survey assessing knowledge and awareness of medicolegal aspects in dental practice. Knowledge was measured with ten specific questions, with scores above 7.5 indicating satisfactory knowledge. Awareness was evaluated using 22 Likert-scale statements, with scores over 66 reflecting high awareness. Statistical analysis, including the Chi-square test, compared knowledge and awareness across different regions and examined these factors’ correlations. The study found no significant differences in medicolegal knowledge and awareness based on practice location (p>0.05). 85.8% of respondents had inadequate knowledge, while 65.7% demonstrated satisfactory awareness. Additionally, workload did not significantly affect knowledge or awareness (p>0.05). Geographic location, workload, and gender do not significantly impact dental practitioners’ medicolegal knowledge and awareness in Indonesia. However, the study highlights a substantial gap in knowledge, underscoring the need for enhanced education and training in this area to improve the legal proficiency of dental professionals. Keywords: Medicolegal; knowledge; awareness; dental practitioner; legal remedy